2012
DOI: 10.1002/wnan.1173
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation studies for the safety assessment of nanomaterials: status quo and the way forward

Abstract: While technical and medical potential offered by nanotechnologies increase, the safety assessment of engineered nanomaterials (NMs) needs to follow this pace. Inhalation is a major route of occupational and environmental exposure, and is most relevant for most of the respective safety assessment studies. Control and generation of aerosol from the test materials for this route of administration are technically demanding, and not surprisingly, there are relatively few NMs tested in toxicokinetic, short-term, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 69 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…Reaching the alveoli, inhaled, uncoated nanoparticles come into contact with pulmonary surfactants forming a 'corona' on the particle surface, which affects particokinetics (Landsiedel et al, 2012). Dispersing agents rendering NM preparations more stable and NMs less likely to sediment are applied in in vitro assays to reflect NM deposition in the lower respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Reaching the alveoli, inhaled, uncoated nanoparticles come into contact with pulmonary surfactants forming a 'corona' on the particle surface, which affects particokinetics (Landsiedel et al, 2012). Dispersing agents rendering NM preparations more stable and NMs less likely to sediment are applied in in vitro assays to reflect NM deposition in the lower respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Landsiedel et al suggested the urgency of performing toxicokinetic and inhalation studies to investigate the hazards associated with NP exposure. 31 The evaporation-condensation method was used to produce AgNP for the investigation of allergic responses after successive inhalation of AgNP in mice, and the principle of the method has been described by Singh et al 20 The advantage of this system is that AgNP can be generated continuously and stably for long-term inhalation within a range of levels, reflecting the natural exposure route for respirable NPs rather than exposure via intratracheal instillation or pulmonary aspiration. Moreover, the SEM-EDX showed that the spherical AgNPs generated by this system were uncontaminated, suggesting that the allergenicity and toxicity observed in this study were attributable to the AgNP.…”
Section: Discussionmentioning
confidence: 99%
“…In Tier 3, the Tier 1 and Tier 2 MG assignment that is based upon non-animal testing alone is confirmed or corrected using data from in vivo short-term studies. For the inhalation route of exposure, i.e., the predominant route of uptake for most nanomaterials (Landsiedel et al 2012a), the rat short-term inhalation study (STIS; Ma-Hock et al 2009a; Landsiedel et al 2014a) is recommended.…”
Section: Decision-making Framework For the Grouping And Testing Of Namentioning
confidence: 99%